Pemerolehan Bahasa Pertama terhadap Anak Usia 2 sampai 4 Tahun Menurut Tataran Morfologi dan Sintaksis - Cita Nugraeni Harsanti (Perkumpulan Kualitama Edukatika Indonesia, 2021)
Language is the main means of communication in human life in this world, both in the form of writing, spoken or only in the form of certain symbols. Without language, humans cannot communicate because humans are social creatures who inevitably have to interact with other humans. Language acquisition in humans begins when children learn to speak. Language acquisition in every child is not the same, according to his age. In this study, children's language acquisition will be studied in terms of morphology and syntax. This study uses a descriptive research method because the research contains an overview of the stage of language pronunciation in children. The data collection technique uses a method with a proficient technique by recording and recording the words spoken by the child. Conclusions in general in the language acquisition of children aged 2 to 4 years can be developed with the stages of morphology and syntax. The researcher found that the process of acquiring discussion was the first at the age of 2 to 4 years, namely the acquisition of morphology, the emergence of free morefemale forms. Second, the acquisition of syntax, the child is able to say several words that can become one word. Third, at the age of 2 to 4 years, the acquisition of morphology and syntax of children begins to perfect in vowel sounds and is also accompanied by consonant sounds.